Author contributions can be clarified. Issue 14 (22nd July 2016) - Ghan, Steven; Crawford, James; Langematz, Ulrike; Leung, Ruby; Li, Zhanqing; Russell, Lynn; Steiner, Allison; Zhang, Chidong
Key Points: Author order is an ambiguous indicator of contribution Greater clarity is needed The optional CrediT standard provides greater clarity